Analisis Faktor Risiko Anemia dalam Kehamilan pada Masa Pandemi Covid-19 - Arnianti Arnianti; Adeliana Adeliana; Hasnitang Hasnitang (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Anemia is one of the factors causing indirect maternal death. Anemia in pregnancy is a condition of mothers with maternal hemoglobin levels of less than 11.0 g / dL in the first and third trimesters and hemoglobin levels of less than 10.5 g / dL in the second trimester. Purpose: Knowing the factors that affect anemia in pregnancy during the Covid-19 pandemic. Methods: This study uses analytical observational studies with a case-control study design. The sampling method uses the Purposive Sampling technique. The sample size in this study was 99 samples consisting of 33 cases and 66 controls. Data were obtained from three health centers in Palopo City: The Bara Permai Health Center, Fort Health Center, and South Wara Health Center. Results: Statistical analysis obtained the age of pregnant women (OR = 7,368; sig (0,000 < 0.05), parity (OR = 2,754; sig = 0.047 < 0.05), pregnancy distance (OR = 2,925; Sig-p=0.022), educate (OR=3.750; sig-p=0.003), adherence to consuming Fe tablets (OR=4.214; Sig-p=0.006, and LiLA status (OR=27.125; Sig-p = 0.000). Conclusion: There is a meaningful influence between the age of pregnant women, parity, gestational distance, education, adherence to Fe tablet consumption, and LiLA status to anemia in pregnancy.